Identification and characterization of cryoprotective peptides extracted from silver carp (Hypophthalmichthys molitrix) hydrolysates - Qingjing Liu; Yongle Liu; Jian Yu; Faxiang Wang; Xianghong Li (International Journal of Food Properties, 2019)
The cryoprotective effects on surimi matrix of hydrolysates with different hydrolyzing times prepared from silver carp using Protamex were compared with commercial sorbitol-sucrose cryoprotectants. Cryoprotective assays showed that FPH-30 (hydrolysate with 30 min hydrolyzing) was a more effective cryoprotectant than other hydrolysates, because the FPH-30 group displayed lower salt-soluble protein extractability loss (29.90 ± 0.84%), less actomyosin Ca2+-ATPase activity decrease (48.85 ± 2.56%) and unfrozen water content decrease (10.39 ± 0.63%) after six freeze-thaw cycles. To exploit industrial utilizations, FPH-30 was further purified with ultrafiltration membranes. The cryoprotective activity of the fraction (<3 kDa) was superior to the others by reducing the salt-soluble protein extractability loss (27.21 ± 0.98%) and impeding the actomyosin Ca2+-ATPase activity decrease (30.54 ± 1.21%). Mass spectrometry analysis showed that the fraction (<3 kDa) was mainly composed of three peptides of the sequences GVDNPGHPFIM(T) and IITNWDDMEK. The results clearly support that silver carp could be a potential source of cryoprotectant peptides for industrial applications.